The nature of syariah compliant problem (SCP) - Abdul Latif Samian (Penerbit Universiti Kebangsaan Malaysia, 2017)
While it is important to find an Islamic solution to every problem in developing an Islamic civilization, it is more important to have an Islamic problem to begin with. Epistemologically, problems are important for the advancement of knowledge in general and science in particular. Suffice it to say that we cannot progress in the absence of problems. From the Islamic perspective, life consists of problems and the way forward in order to achieve taqwa is by solving problems. Ditto for building an Islamic product, family, organization, society or nation which must be base upon knowledge. Accordingly, Islamization of knowledge is Islamization of problems because not all problems are Islamic and scholars, scientists included, cannot achieve taqwa by mitigating problems that are unislamic. A problem is unislamic if it is not syariah compliant. In this article, we examine the ontological aspects of syariah compliant problems (SCP) and provide the outline of the methodology of scientific research that stems from SCP.